Nepal - Stads, Gert-Jan; Shrestha, Hari K.; Nin-Pratt, Alejandro; Pham, Nguyen Thi (International Food Policy Research Institute, 2019)
Agricultural research investment and human resource capacity in Nepal have grown rapidly in recent years in response to increased government funding; in 2016, the country invested 0.42 percent of its AgGDP in agricultural research. NARC is by far the largest agency conducting agricultural research, accounting for nearly 80 percent of Nepal’s agricultural research investments and human resource capacity. Nepal’s research agencies lack the infrastructure and critical mass of researchers needed to address the multidisciplinary challenges the agricultural sector is facing. It is important that recent government support be sustained in the long run.